Conversion of glycerol to polyglycerol over waste duck-bones as a catalyst in solvent free etherification process - Ayoub, M. (Institute of Physics Publishing, 2017)
The alkaline catalyst derived from the duck-bones was used for conversion of glycerol to polyglycerol via solvent free etherification process. The physicochemical properties of prepared materials were duck-bones were systematically investigated as a catalyst by latest techniques of Thermo gravimetric analysis (TGA), X-ray diffraction (XRD), and Brunauer-Emmett-Teller (BET) surface properties. TGA showed different trends of duck-bones decomposition from room temperature to 1000C. XRD pattern showed a clear and sharp peaks of a crystalline phase of CaO. The activity of the catalysts was in line with the basic amount of the strong base sites, surface area, and crystalline phase in the catalysts. The prepared catalyst derived from duck-bones provided high activity (99 ) for glycerol conversion and around 68 yield for polyglycerol production. These ample wastes of duck-bones have good potential to be used as polyglycerol production catalysts due to have high quantity of Ca compare to other types of bones like cow, chicken and fish bones. © Published under licence by IOP Publishing Ltd.